2020
DOI: 10.1017/s1751731119002817
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of traits for characterizing feed intake patterns in dairy goats: a basis for phenotyping in the precision farming context

Abstract: In ruminants, feeding behaviour variables are parameters involved in feed efficiency that show variation among individuals. This study aimed to evaluate during the first two production cycles in ruminants the repeatability of feed intake pattern, which is an important aspect of feeding behaviour. Thirty-five dairy goats from Alpine or Saanen breeds were housed in individual pens at four periods (end of first gestation, middle of first and second lactations and middle of second gestation which is also the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A previous study in individually housed goats (Giger-Reverdin et al, 2019) has shown a good repeatability of individual feeding behaviour between the end of their first gestation and the middle of their second gestation. Our study also showed a good repeatability between goats tested in mid-and late lactation.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…A previous study in individually housed goats (Giger-Reverdin et al, 2019) has shown a good repeatability of individual feeding behaviour between the end of their first gestation and the middle of their second gestation. Our study also showed a good repeatability between goats tested in mid-and late lactation.…”
Section: Discussionmentioning
confidence: 81%
“…Using this method, we were able to determine six variables of feeding behaviour (Table 1). In accordance with previous work (Giger-Reverdin et al, 2019), special emphasis was given to the first meal after feed delivery.…”
Section: Intake Measurements and Determination Of Mealsmentioning
confidence: 90%
See 2 more Smart Citations
“…The index described here allows ranking of ruminants for their capacity to buffer the effect of a highly fermentable diet, and subsequently refining strategies to select for animals more resistant to SARA. Finally, in livestock precision farming, this index helps to adapt feed composition to an animal’s rumen capacity and thereby efficiently valorise food composition 12 .…”
Section: Introductionmentioning
confidence: 99%